Analysis of Trust through Academic Information System and Image of Private University - Realize, Realize (Archives of Business Research, 2018)
Private universities must have a uniqueness that distinguishes them from others and it becomes a distinctive feature that gives its own appraisal in the hearts of people. This uniqueness can grow a good image and can bring public confidence. Efforts to build trust for a university absolutely must be done in order to maintain existence. This study aims to analyze trust through the use of academic information systems and private university image. Result of the research based on hypothesis analysis and test show that academic information system has significant influence on direct image and trust of private universities in province of Kepulauan Riau.